The rational design of a Au(I) precursor for focused electron beam induced deposition - Marashdeh, Ali; Tiesma, Thiadrik; van Velzen, Niels J. C.; Harder, Sjoerd; Havenith, Remco W. A.; De Hosson, Jeff T. M.; van Dorp, Willem F. (Beilstein Journal of Nanotechnology, 2017)
Au(I) complexes are studied as precursors for focused electron beam induced processing (FEBIP). FEBIP is an advanced direct-write technique for nanometer-scale chemical synthesis. The stability and volatility of the complexes are characterized to design an improved precursor for pure Au deposition. Aurophilic interactions are found to play a key role. The short lifetime of ClAuCO in vacuum is explained by strong, destabilizing Au–Au interactions in the solid phase. While aurophilic interactions do not affect the stability of ClAuPMe3, they leave the complex non-volatile. Comparison of crystal structures of ClAuPMe3 and MeAuPMe3 shows that Au–Au interactions are much weaker or partially even absent for the latter structure. This explains its high volatility. However, MeAuPMe3 dissociates unfavorably during FEBIP, making it an unsuitable precursor. The study shows that Me groups reduce aurophilic interactions, compared to Cl groups, which we attribute to electronic rather than steric effects. Therefore we propose MeAuCO as a potential FEBIP precursor. It is expected to have weak Au–Au interactions, making it volatile. It is stable enough to act as a volatile source for Au deposition, being stabilized by 6.5 kcal/mol. Finally, MeAuCO is likely to dissociate in a single step to pure Au.
Keywords: crystallography; focused electron beam induced processing; gold chemistry; precursor design